Pomegranate-peel-chitosan-gelatin composite: A hemostatic dental sponge with antibacterial enhancement - Lale Rozykulyyeva; Prihartini Widiyanti; Sirojuddin Kholil Muhammad; Suryani Dyah Astuti (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Effective post-tooth extraction bleeding management and the alleviation of patient discomfort hinge upon the careful choice and judicious application of suitable hemostatic agents. Purpose: In this study, we developed a biodegradable, porous hemostatic sponge composed of gelatin (GE) and chitosan (CS), enhanced by the incorporation of pomegranate peel extract (PE), which was designed for use in dental applications, with a focus on antibacterial properties and infection prevention. Methods: The sponge was synthesized using an environmentally friendly (green) foaming approach without a foaming agent and was fabricated by freeze-drying. The efficiency of the hemostatic sponge was evaluated using various tests, including structural analysis, mechanical strength, water absorption capacity, hydrophilicity, blood clotting time (BCT), in vitro antibacterial effectiveness, and biodegradability. Results: The calcium chloride–crosslinked CS-GE and PE-immersed (CS-GE-PE) sponges exhibited adequate tensile strengths, with CS-GE-PE at 0.776 ± 0.025 MPa. The CS-GE-PE sponge showed significant water absorption (927.1% ± 37.55%). Hydrophilicity was evident (contact angle: 45°) and decreased slightly with the addition of PE. The BCT was shorter for the CS-GE sponge (161 ± 9.644 s), and both sponges exhibited minimal hemolysis, indicating biocompatibility. The CS-GE-PE sponge exhibited slightly enhanced antibacterial properties. Conclusion: This study has successfully developed a composite sponge consisting of CS, GE, and PE that exhibits a balanced level of biodegradability, antibacterial and anti-inflammatory properties, and blood absorption properties that reduce clotting time. This innovative material has great potential for a wide range of clinical applications in dental procedures and wound care.